2023
DOI: 10.1186/s12906-023-04200-8
|View full text |Cite
|
Sign up to set email alerts
|

Anti-malarial and haematological evaluation of the ethanolic, ethyl acetate and aqueous fractions of Chromolaena odorata

Tobiloba Christiana Elebiyo,
Olarewaju Michael Oluba,
Oluyomi Stephen Adeyemi

Abstract: Malaria is a global health challenge with endemicity in sub-Saharan Africa, where there are multiple drug-resistant strains and limited access to modern health care facilities, especially in rural areas. Studies indicate that African traditional medicine could make a substantial contribution to the reduction of malaria-related deaths and achievement of universal health coverage (UHC), particularly in these regions. Thus, this study evaluated the curative antimalarial effects of Chromolaena odorata leaf extract… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
2
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Neutrophil and lymphocyte percentages, which are markers of inflammation and immune response, were notably normalized by Nm treatment. These findings imply that Nm ethyl acetate leaf fraction could mitigate diabetic-induced haematological abnormalities (38), potentially through anti-inflammatory and erythropoietic mechanisms, warranting further investigation for clinical application (39).…”
Section: Discussionmentioning
confidence: 87%
“…Neutrophil and lymphocyte percentages, which are markers of inflammation and immune response, were notably normalized by Nm treatment. These findings imply that Nm ethyl acetate leaf fraction could mitigate diabetic-induced haematological abnormalities (38), potentially through anti-inflammatory and erythropoietic mechanisms, warranting further investigation for clinical application (39).…”
Section: Discussionmentioning
confidence: 87%
“…A vast array of secondary metabolites or bioactive compounds in C. odorata can be of anticancer, antidiabetic, anti‐malarial, anti‐inflammatory, antimicrobial, and antiparasitic medicinal applications (Elebiyo et al, 2023; Olawale et al, 2022). However, the medicinal values of C. odorata were noted mostly in African and Asian context, therefore cannot be generalized at global scale (Mugwedi, 2020).…”
Section: Beneficial Aspectsmentioning
confidence: 99%
“…Folklore studies reported that the C. odorata is widely used in treatment of diabetes and in this vein a recent molecular study revealed that its extract can potentially regulate Nrf2/keap1 antioxidant pathway to prevent the diabetes induced liver dysfunction (Elekofehinti et al, 2023). Leaf extracts C. odorata were also clinically tested with mouse model which revealed their potential in malaria therapy, especially in sub‐Saharan Africa (Elebiyo et al, 2023). The antioxidative potential and phenolic content of C. odorata can combat ROS which can further be exploited in human healthcare to treat diseases (e.g., cancer, diabetes, cardiovascular diseases, aging, and cellular apoptosis) (Halliwell & Gutteridge, 1999; Ozsoy et al, 2008).…”
Section: Beneficial Aspectsmentioning
confidence: 99%